Countering demand for ineffective health remedies: Do consumers respond to risks, lack of benefits, or both?. Issue 5 (4th May 2021) - MacFarlane, Douglas; Hurlstone, Mark J.; Ecker, Ullrich K. H.
Abstract: Objective: We tested whether targeting the illusion of causality and/or misperceptions about health risks had the potential to reduce consumer demand for an ineffective health remedy (multivitamin supplements). Design: We adopted a 2 (contingency information: no/yes) × 2 (fear appeal: no/yes) factorial design, with willingness-to-pay as the dependent variable. The contingency information specified, in table format, the number of people reporting a benefit vs. no benefit from both multivitamins and placebo, plus a causal explanation for lack of efficacy over placebo. The fear appeal involved a summary of clinical-trial results that indicated multivitamins can cause health harms. The control condition received only irrelevant information. Main outcome measure: Experimental auctions measured people's willingness-to-pay for multivitamins. Experiment 1 ( N  = 260) elicited hypothetical willingness-to-pay online. Experiment 2 ( N  = 207) elicited incentivised willingness-to-pay in the laboratory. Results: Compared to a control group, we found independent effects of contingency information (-22%) and the fear appeal (-32%) on willingness-to-pay. The combination of both interventions had the greatest impact (-50%) on willingness-to-pay. Conclusion: We found evidence that consumer choices are influenced by both perceptions of efficacy and risk. The combination of both elements can provide additive effects that appear superior to either approach alone.